Study of Making of Instant Noodle Using Composite Wheat Flour, Four Variety of Sweet Potato Flour, and Mung Bean Flour - Guntur Kurniawan Hasibuan; Ismed Suhaidi; Terip Karo-Karo (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The research was aimed to study of making of instant noodle using composite wheat flour, four variety of sweet potato flour and mung bean flour, and to formulate the best  sweet potato variety to make instant noodle. The research had been performed using factorial completely randomized design, with one factor i.e : ratio of wheat composite flour, four variety of sweet potato flour, and mung bean flour (G) : 70%:20%:10%, 70%:20%:10%, 70%:20%:10%, 70%:20%:10%, 70%:15%:15%, 70%:15%:15%, 70%:15%:15%, 70%:15%:15%, 70%:10%:20%, 70%:10%:20%, 70%:10%:20%, 70%:10%:20%. Parameters analyzed where water content, ash content, fat content, fiber content, protein content, carbohydrate content, water absorption, lost of solid on cooking, colour organoleptic score, taste organoleptic value, elasticity organoleptic value, springy organoleptic value. The research showed that the ratio of wheat composite flour, four variety of sweet potato, and mung bean flour had highly significant effect on water content, ash content, fat content, fiber content, water absorption, lost of solid on cooking, colour organoleptic score and taste organoleptic value and had significant effect on protein content and carbohydrate content but had no signifnicant effect on elasticity orgonelptic value and springy organoleptic value. The formulation of 70%:10%:20%  with white sweet potato variety was the best for the making instant noodle. Keyword: Wheat flour, four variet of sweet potato flour, mung bean flour, instant noodle.